Quality of self-management among diabetes mellitus patient - Rapitos Sidiq; Widdefrita Widdefrita; John Amos; Novelasari Novelasari; Mahaza Mahaza; Ismail Ismail (International Journal of Public Health Science (IJPHS), 2021)
Diabetes mellitus is a chronic disease that has very high morbidity and mortality rate. This disease cannot be cured but can be controlled with good self-management. This research determined the quality of self-management of diabetics at community health centers in Padang City in 2019. This is a descriptive-analytic study with amount of samples 105 people with diabetes. Data collection was carried out from July to November 2019 at seven community health centers in Padang City, namely: Nanggalo, Lapai, Alai, Andalas, Ambacang, Kuranji and Pauh community health centers. Data were collected by interviewing and processed by the stages of coding, editing, tabulating, and transferring. Data were analyzed by bivariate and multivariate analysis (Chi-square and logistic regression) with a significant level of 0.05 (5%). The results showed that 60% of the quality of self-management in good category. Factors that significantly affect the quality of self-management are physical exercise/sports (p-value=0.003), education (p-value=0.006) and regularity of taking medication (p-value=0.021). The quality of self-management is largely good and physical exercise greatly affects the quality of self-management of diabetes mellitus patients.